Biodiversity post‐2020: Closing the gap between global targets and national‐level implementation. Issue 2 (21st November 2021) - Perino, Andrea; Pereira, Henrique M.; Felipe‐Lucia, Maria; Kim, HyeJin; Kühl, Hjalmar S.; Marselle, Melissa R.; Meya, Jasper N.; Meyer, Carsten; Navarro, Laetitia M.; van Klink, Roel; Albert, Georg; Barratt, Christopher D.; et al.
Abstract: National and local governments need to step up efforts to effectively implement the post‐2020 global biodiversity framework of the Convention on Biological Diversity to halt and reverse worsening biodiversity trends. Drawing on recent advances in interdisciplinary biodiversity science, we propose a framework for improved implementation by national and subnational governments. First, the identification of actions and the promotion of ownership across stakeholders need to recognize the multiple values of biodiversity and account for remote responsibility. Second, cross‐sectorial implementation and mainstreaming should adopt scalable and multifunctional ecosystem restoration approaches and target positive futures for nature and people. Third, assessment of progress and adaptive management can be informed by novel biodiversity monitoring and modeling approaches handling the multidimensionality of biodiversity change.